2018
DOI: 10.2146/ajhp170405
|View full text |Cite
|
Sign up to set email alerts
|

Use of clinical decision support to identify i.v.-to-oral conversion opportunities and cost savings

Abstract: Hospital pharmacists' i.v.-to-oral conversion practices with the CDS tool resulted in medication cost savings of 9%, or $1.48 million, for 13 medications evaluated over a 6-month period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Previous studies have shown that IV to PO conversion programs can increase PO utilization and reduce drug costs [4][5][6][7][8][9][10]. Our study results highlight the positive impact that the revision of an ASP program's pre-existing IV to PO conversion criteria and protocol can have to decrease IV medication utilization rates and increase PO utilization, resulting in overall decreased costs.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies have shown that IV to PO conversion programs can increase PO utilization and reduce drug costs [4][5][6][7][8][9][10]. Our study results highlight the positive impact that the revision of an ASP program's pre-existing IV to PO conversion criteria and protocol can have to decrease IV medication utilization rates and increase PO utilization, resulting in overall decreased costs.…”
Section: Discussionsupporting
confidence: 51%
“…Most studies (n = 50) reported on interventions that used more than 1 approach to optimize ePrescribing systems (Table 3). 4,41–94 Table 3 summarizes the various combinations of optimization strategies and intervention components that were used in the included studies and the overall reported effectiveness of the intervention on the primary outcome.…”
Section: Resultsmentioning
confidence: 99%
“…The commercially available clinical surveillance software used by the health system was external and separate from the electronic health record (EHR) system. The software aligned data with a library of >3,000 algorithms ("rules"; Carver et al, 2018) and served as the primary software pharmacists used in their daily workflow. If rule requirements were satisfied, the software created an alert.…”
Section: Preimplementation Clinical Pharmacist Workflow Alert Managementmentioning
confidence: 99%
“…For these reasons, some health systems use clinical surveillance software to notify pharmacists of clinical opportunities to maximize workflow efficiency, thereby increasing the number of interventions completed per patient (Calloway et al, 2013). Clinical surveillance software notifies pharmacists of possible adverse drug events (ADEs), intravenous (IV)-to-oral-medication conversion opportunities, renal dose adjustment opportunities, culture surveillance updates, extended duration of antibiotic therapy, and duplicate therapy interventions (Calloway et al, 2013; Carver et al, 2018; Hamblin et al, 2012; Huber et al, 2016; Jha et al, 2008; Kawamoto et al, 2005; Rech, Adams, et al, 2021; Rech, Gurnani, et al, 2021). Optimized pharmacist workflows that result in completed interventions reduce adverse events, increase cost savings, and improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation